The intensity of conflict, growth and post-conflict recovery - Michael Bleaney; Arcangelo Dimico (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2011)
Growth rates of per capita GDP are depressed by civil conflict to a degree that reflects its severity. Only the more severe conflicts - ones that affect at least half of the country by land area and/or cause more than 1,000 fatalities in at least one year - have a significant negative growth effect. Post-conflict recovery of output is enhanced by aid flows but this finding may be subject to endogeneity bias.
Keywords: O1; O4; 330; aid; conflict; growth; Konflikt; Bürgerkrieg; Entwicklungshilfe; Wirtschaftswachstum